An Odd Way of Looking at Things (LEARNing Landscapes, 2022)
IIn this interview, actor, writer, and comedian Mary Walsh discusses how comedy is part and parcel of Newfoundland‘s social fabric. She recounts her early days in theatre, which soon led to her forming comedy troupes with performers who would become lifelong collaborators. She outlines the basic skills for becoming a comedian as well as the challenges of being an older woman in comedy. In conclusion, she poignantly connects comedy to the importance of knowing one‘s history: “A bit of comedy helps the truth go down . . . they always say the truth will set you free. It‘ll make you mad first, but it‘ll make you free . . . We found right across the country that people were very open to the message because they got it with a laugh . . .“
Keywords: comedy; Newfoundland; activist